Propolis attenuates diabetes-induced testicular injury by protecting against DNA damage and suppressing cellular stress - Ashour, Ahmed M. (Frontiers in Pharmacology, 2024)
Propolis has a wide range of biological and pharmacological actions, including antioxidant properties, particularly its phenolic and flavonoid constituents, that could potentially protect the reproductive system from oxidative damage.Four groups of forty male Wistar rats each were allocated. The vehicle was given to the first group's normal control rats (NC). The second, third, and fourth groups of diabetic rats were given vehicle (diabetic control) and propolis orally at 50 and 100 mg/kg, respectively, for eight weeks. Diabetes was induced in rats via injection of nicotinamide (NA) and streptozotocin (STZ). Fasting blood glucose (FBG) and insulin levels, homeostatic model assessment for insulin resistance (HOMA-IR), and semen analysis were assessed. Added to that, assessments of serum reproductive hormones, including total testosterone (TTST), estradiol (E2), follicle-stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL), were measured at the end of the study. As well, tissue TTST, E2, and dihydrotestosterone (DHT) were evaluated. Serum and tissue oxidative enzymes, including catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) activities, was carried out, and malondialdehyde (MDA) content was determined. The pancreatic and testicular tissues were histopathologically examined, and proliferating cell nuclear antigen (PCNA) and B-cell lymphoma 2 (Bcl-2) in testicular tissue were immunohistochemically analyzed. Testicular tissue was examined for DNA integrity using a comet assay. Compared to the STZ-control group, propolis greatly decreased FBG levels and improved the glycemic status of diabetic rats. In comparison to the STZ-DC group, propolis increased the number of sperm cells and the percent of morphologically normal and viable sperm in male rats, improving their fertility.Propolis also restored the pancreatic islets, protected the testis from oxidative stress, and increased levels of reproductive hormones in the blood, especially testosterone. Moreover, propolis at high doses demonstrated a strong positive response for Bcl-2 and a negative expression of PCNA in spermatogenic cells. In summary, the data obtained indicate a strong indication that STZ causes severe impairments to the testis, whereas propolis, acting as an antioxidant, protects against the adverse effects of STZ on the testis.